Etik Pendidikan Karakter dalam Novel A+ sebagai Antologi Pembelajaran Apresiasi Sastra di SMA - Pramita, Nadya Wahyu; Kuncoro, Syaharani Zahra ‘Aisy (Lembaga Yasin AlSys, 2023)
The purpose of character value education is to increase self-empowerment and build better character through learning methods. In addition, this study aims to discuss the values of character education contained in Ananda Putri's Novel A+. The researcher will discuss the novel's intrinsic value, the psychological state of the characters, and its relevance as an anthology for teaching literary appreciation in senior high schools. This study determines Novel A+ because it shows a person's efforts to achieve his goals and also has character education values. These values include educational, moral, and social values. The issues that will be discussed include: (1) The intrinsic elements as the builders of A+ novels, such as theme, plot, characters, characterization, setting, point of view, and style of language, which are included in the formulation of this research problem, (2) What are the the ethics of character education in Novel A+, and (3) What are the descriptions of the ethics of character education in Ananda Putri's Novel A+ as an anthology of teaching literary appreciation in high school?